Śrī Jayavardhanapura Kōṭṭē lēkhaka toraturu - Paññāśēkhara, Dēvahandiyē, Himi (Saṃskrtika Kaṭayutu Amātyāṃśaya, 1984)
Historical survey of the contribution of litterateurs of Kōṭṭe (Jayavardhanapura) to Sinhalese literature.